Brief tele-mindfulness-based intervention: A multicenter randomized controlled trial - Amani M AlQarni; Abdulaziz Elfaki; Moataza M Abdel Wahab; Yasser Aljehani; Auday A Alkhunaizi; Johnson Alex; Sharifa A Othman; Fatma H Amer; Faisal A Alghamdi; Khalid A Alissa (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Coronavirus disease 2019 (COVID-19) has proven to be detrimental to the psychological well-being of healthcare providers (HCP). This study was a psychological intervention during the COVID-19 pandemic to check extent to which brief mindfulness-based interventions (MBIs) and progressive muscle relaxation (PMR) affect psychological well-being, resilience, and anxiety of HCPs. MATERIALS AND METHODS: A randomized trial study conducted from July to August 2020. One hundred and forty-seven COVID-19 frontline HCPs were randomized to a 2-week virtual intervention with a brief MBI or a PMR. Pre- and postintervention assessments were done using the State-Trait Anxiety-20-Item Scale, the Connor-Davidson Resilience Scale-10, and WHO-5 Well-Being Index. RESULTS: The final sample included 125 HCPs (64 in BMI group and 61 in PMR group) who completed pre- and post-intervention assessment. The results showed a significant improvement in the psychological well-being and reduction of the state anxiety of the two groups, but not in the trait anxiety or resiliency. Improvement was more in the group's brief MBI (81.3%) than in the group's PMR (51.8%) (P = 0.0001), concerning psychological well-being. CONCLUSION: Both the brief MBI and PMR improved the psychological well-being and reduced the anxiety of frontline healthcare providers during the COVID-19 pandemic with a slightly better improvement in the brief MBI.